Diet Fosfor Tinggi Penyebab Osteodistrofia Fibrosa pada Tikus (HIGH PHOSPHOROUS DIET CAUSED OSTEODISTROFIA FIBROSA IN RATS) - ., Hartiningsih; Wasito, Raden (Jurnal Veteriner; Vol 14 No 1 (2013), 2013)
The objective of this research was to study the impact of high phosphor diet on the femur of ratsconsuming soybean. Ten female rats at 4 weeks of age were randomly divided into two groups of five, NP(rats fed with normal phosphor diet) and HP (rat fed with high phosphor diet). Each rats was placed intoindividual cages at 22-25°C. All  rats were given normal diet and water which were  provided ad libitum.The rats were also adaptation for three weeks before the treatment was given.  At seven weeks of age, ratsin NP group were fed normal diet (calcium:phosphor=0,6%:0,4%), while rats in HP group were fed highphosphorus diet (calcium:phosphor=0,6%:3,6%) for 6 weeks. At the end of the study, blood was collectedfrom plexus retroorbitalis for calcium and phosphor analysis, while right femur was taken forhistopathological examination using hematoxylin and eosin stain. The research results showed that bloodof calcium was significantly reduced (P<0.01) in HP group compared with NP group, while blood phosphorwas significantly increased (P<0.01) in HP group. Histopathological analysis of the proximalis femur inNP group showed the osteogenic zone of physis and the trabecular bone speculum of metaphysis werenormal, while the osteogenic zone of physis and the trabecular bone speculum of metaphysis in HP groupwere irregular.  Fibroblast in  trabecular bone speculum of bone marrow were also observed.  It can beconcluded that high phosphorus diet may cause osteodystrophia fibrosa in rats.
Keywords: phosphorous, osteodystrophia fibrosa, calcium, soybean